The effectiveness of McMaster model on anxiety and self-control of women on the verge of divorce - Delfanazari, Ramin; Behbodi, Masoumeh; Dokaneifard, Farideh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of McMaster model on anxiety and self-control of women on the verge of divorce. Method: The present study was a quasi-experimental with pre-test and post-test with a two-month control and follow-up group; The statistical population of the present study was women referring to counseling centers in District 6 of Tehran in 2020. After screening with the Zung Anxiety Questionnaire (1971), 30 women were selected by convenience sampling method in the experimental group of McMaster model (n = 15) and control group (n = 15) were randomly replaced. The experimental group underwent the intervention of McMaster model (2007) for eight sessions of 90 minutes and the control group did not receive any intervention. The research instruments were Zung Anxiety Inventory (1971) and Tangney, Bamster and Boone (2004) Self-Control Questionnaire and the data were analyzed using repeated measures mixed variance analysis. Results: The results showed the effect of Maxmaster model intervention on anxiety score (F = 5.25, P = 0.030) and self-control (F = 8.56, P = 0.007) and the stability of this effect in the follow-up stage. Conclusion: The results of the study suggest evidence that the McMaster model is an appropriate method to increase self-control and also reduce anxiety in women on the verge of divorce.